Trauma Group Therapy with African American Children and Adolescents: A 30-plus Year Content Analysis. Issue 1 (2nd January 2020) - Manyam, Suneetha B.; Davis, Terah L.
ABSTRACT: Group therapy plays a prominent role in trauma healing through resiliency for African American children and adolescents. Understanding how groups can facilitate change for this population is crucial to become a culturally competent counselor. Further, studying the best practices of group work is essential to better serving African Americans. Through a content analysis of scientific literature from 1980 to 2018 on trauma and group work with African American children and adolescents, authors explore the common themes that emerged. Counseling implications from an advocacy and multicultural perspective along with future recommendations are discussed at the end.